KLAUSULA EKSONERASI DALAM PERJANJIAN KREDIT ANTARA PT. MANDIRI PERSERO (TBK) SEMARANG DENGAN WIBOWO S.E. DAN SITI AISYAH (Studi Kasus Putusan No. 8 K/Pdt/2013) - Hellen Rumiris; Stanislaus Atalim (Jurnal Hukum Adigama, 2018)
Granting credit by the bank to the society greatly helps to develop a business that is run by community both individuals and legal entities. The government of the Republic of Indonesia has intructed banking to provide credit facilities especially for the middle and lower businesses. Banking credit agreement is a standard contract made by the bank by almost not giving freedom at all to the other parties to do negotiation for the requirements offered. This type of research using a normative juridicial research. This research aims to analyze the exoneration clauses in a credit agreement between PT. Bank Mandiri Persero (Tbk) Semarang with Wibowo, S.E. and Siti Aisyah. The bank credit agreement is the legal agreement to the Article 1320 of Indonesian Civil Code. However, the exoneration clauses listed on it contradicts some basis in the law agreement and also violates the provisions of Article 18 of The Consumer Protection Act. Clauses in a credit agreement are made to regulate the rights and the obligatons of the parties so that reasonable risk sharing occures between the bank and the customer. In fact, exoneration clauses are often abused by businessman attempting to diminish, divert and even refuse responsibility. The result of this research concludes that: First, the Government must provide more limits on the using of exoneration clauses through revision of The Consumer Protection Act. Second, PT. Bank Mandiri (Tbk) Semarang must be more meticulous and careful to determine contents of credit agreement.